Assessment of Suicide Attempt in The Forensic Medicine Outpatient Clinic in Muğla - Kıymet, Muazzez Elçin; Ünüvar Göçeoğlu, Ümit; Yürürdurmaz, Betül; Balcı, Yasemin (The Bulletin of Legal Medicine, 2020)
Objective: Suicide attempts are causes of mortality and morbidity. Suicide attemp patients’ reports were evaluated in Forensic Medicine outpatient clinic. It was aimed to present of sociodemographic characteristics, methods, regional characteristics, develop to recommendations for proventive measures. Materials-Methods; Between 01.06.2014-31.12.2018 were evaluated retrospectively and statisticaly. Results: 405(5.3%) of the cases attempted suicide, 263(64.9%) were women, 142(35.1%) were men, 11.8% of them (n: 48) was under 18, 84.9% (n: 344) was under 40. The majority of the cases were in the 20-29 age range, women were more present in under 19 years, and men were more present in the 30-39 age group(p <0.001). No significant difference was found between months and seasons. The most common method was drugs (86.2%, n: 349), followed by knife wound (8.9%,n:36) hanging (2.2%,n:9). In terms of severity of injury; It was found that 3.2% of the cases had a life-threatening injury, 88.4% of them were mild with simple medical intervention and 8.4% were mild. Discussion and Conclusion: The most common methods were drug. One of the striking results that, the rate of attempting suicide of women under 19 years of age is higher than men, men in the 30-39 age group is higher. In this result for women; the search for identity the roles of society expectation and the restrictions of freedom play role, for men; economic reasons, responsibilities play a role. The findings are important to shed light on protective measures. It would be useful to refer the patients who applied to social support units.